Implementation and Development of Digital Technology-Based Entrepreneurial Skills of Vocational Education Teacher Candidate Students - Sultono Sultono; Lady Januasti Merdian; Agung Ridho Rohim (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
Abstract: This study aims to analyze the implementation and development of digital technology-based entrepreneurial skills among prospective vocational education teacher students. Using a mixed method approach with a sequential exploratory design, the study involved 180 students from ten prospective teacher education study programs at the Faculty of Engineering and Industrial Education, Universitas Pendidikan Indonesia. Data were collected through surveys, in-depth interviews, learning observations, and analysis of digital products developed by students. The results of the study indicate that the implementation of digital entrepreneurship learning can improve students' abilities in identifying business opportunities, using digital platforms for business development, and creating innovative technology-based solutions. The main determinants include individual factors such as self-efficacy and experience, institutional factors, especially technological infrastructure and lecturer competence, and environmental factors such as industry partnerships and stakeholder networks that contribute to the level of quality and innovation of entrepreneurial output. Based on the research findings, the Integrated Digital Entrepreneurship Learning (IDEL) Model has proven effective in developing student abilities. Challenges faced are the digital literacy gap, limited internet access, and lack of curriculum integration. The study recommends the development of an integrated learning model, improving lecturers' digital competence, and strengthening the digital entrepreneurship ecosystem in higher education. Keywords: digital entrepreneurship, prospective teachers, vocational education, digital technology, learning innovation